Color adaptation of videos for mobile devices - Ang, Fu Li (2009)
As technology improves rapidly over the recent years, watching videos on mobile devices is no longer a dream. In the past, videos are, more often than not, only played on television or personal computers. Nowadays, the improvements in technology have made the playback of videos on mobile devices possible. However, this is not without any problems. In terms of video quality, videos that are played on mobile devices still pales in comparison with videos played on television or personal computers.